2008
DOI: 10.1159/000127442
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Rosuvastatin and Atorvastatin when Force-Titrated in Patients with Primary Hypercholesterolemia

Abstract: Background: Patients at high risk of cardiovascular disease frequently fail to reach recommended low-density lipoprotein cholesterol (LDL-C) goals, partly because statin doses are not titrated to optimal effect. The ECLIPSE study was designed to compare the efficacy and safety of force-titrated treatment with rosuvastatin (10–40 mg) with that of atorvastatin (10–80 mg) in high-risk patients with hypercholesterolemia. Methods: In this 24-week, open-label, randomized, multinational, parallel-group study, 1,036 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…The mode of actions of statins and their effects on lipids and apos is reviewed in more detail elsewhere (163)(164)(165). The most commonly used drugs today are the statins that can reduce apoB synthesis and increase apoA-I synthesis and turnover.…”
Section: Effects Of Lipid-lowering Therapy On Change Of Apob Apoa-i mentioning
confidence: 99%
See 2 more Smart Citations
“…The mode of actions of statins and their effects on lipids and apos is reviewed in more detail elsewhere (163)(164)(165). The most commonly used drugs today are the statins that can reduce apoB synthesis and increase apoA-I synthesis and turnover.…”
Section: Effects Of Lipid-lowering Therapy On Change Of Apob Apoa-i mentioning
confidence: 99%
“…The most effective apoB-reducing statins are atorvastatin and rosuvastatin which lower the apoB-values by about 40-45% and 45-50%, respectively. Best increase in apoA-I concentrations is obtained by rosuvastatin which can increase the value by about 10-15% depending on baseline values, the lower the higher is the increase (163)(164)(165). Commonly for all statins there is a strong dose-response relationship, except for atorvastatin where higher doses commonly result in lowering of HDL-C and apoA-I values.…”
Section: Effects Of Lipid-lowering Therapy On Change Of Apob Apoa-i mentioning
confidence: 99%
See 1 more Smart Citation
“…7 They use the results of this trial in marketing. See, for example, http://www.crestor.com/c/about-crestor/crestorclinical-studies.aspx, andFaergeman et al (2008) for the clinical trial results.8 Congress specifically sent a letter to the FDA to challenge marketing of Vytorin(Mathews (2008)). 9 The study was completed in 2006.…”
mentioning
confidence: 99%
“…Despite these differences, the authors concluded that rosuvastatin and atorvastatin were similarly well tolerated [61]. The study showed that increasing doses of rosuvastatin produced a dose-related increase in the incidence of proteinuria (from 0.2 to 1.8%) and hematuria (from 2.9 to 4.0%), whereas this effect was not apparent with atorvastatin.…”
Section: Are All Statins Equally Effective In Reducing Proteinuria Anmentioning
confidence: 96%